INSTITUTIONAL ASPECTS OF MANAGEMENT OF SOCIO-CULTURAL DEVELOPMENT OF TERRITORIAL COMMUNITIES IN THE CONDITIONS OF WAR AND POST-WAR RECONSTRUCTION - KHUDYK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Socio-cultural development is a key aspect of citizens’ lives, fostering national unity, patriotism, and strengthening civil society. Cultural events play a formative civic role and enhance the country’s investment appeal. The concepts of "culture," "socio-cultural activity," and "socio-cultural space" encompass all spheres of life, from material to spiritual. Socio-cultural activity involves the creation and dissemination of cultural values, supporting creativity and communication, contributing to the development of civic identity and personal self-awareness—foundations for community cohesion. During wartime, the role of culture intensifies, ensuring societal stability, preserving identity, and resisting efforts to eradicate the Ukrainian nation. Russia’s aggression targets not only physical destruction but also the cultural and national identity of Ukraine. Despite the threat, support for Ukraine’s cultural sector remains limited, especially from the state and business; most assistance comes from international organizations, volunteers, and civil initiatives. Major challenges include outdated infrastructure, unstable funding, low wages, staff shortages, weak digitalization, and declining public interest. Decentralization has empowered local communities with more responsibilities in cultural development, unlocking potential for local identity, tourism, and economic growth, yet posing difficulties in cultural management and accessibility of services. This study analyzes institutional aspects of socio-cultural management within the decentralization reform and war context. It identifies structural, legal, and organizational relations, challenges to development, and offers proposals to improve conditions for cultural growth and post-war recovery. Using a systems approach and methods such as content and comparative analysis, expert evaluation, SWOT analysis, induction and deduction, the research concludes that management efficiency depends on institutional capacity and adaptability. Recommendations are made to strengthen human capital, infrastructure, digitalization, and equal access to culture.